Phytosociological study of the tree stratum of a semideciduous mesophytic forest in the municipality of Botucatu, SP, Brazil - Gabriel, JLC; Pagano, S. N. (Inst Tecnologia Parana, 1992)
The phytosociological structure was studied in an area of semideciduous mesophytic forest lied on the ascent of the Cuesta of Botucatu. Once the relief of the area was very heterogeneous, the forest, for the sampling process, was divided in three sampling regions: the upper one (on the plateau), the middle one (on the ascent properly said) and the lower one (on the plain). Through the point-centered method, 1224 (408 in each region) trees were sampled. For this work, only the trees with shaft equal or higher than 1.30m high were considered. The three sampling regions showed some interesting differences in regard to the phytosociologic structure. Once there are differences among the soil of the three regions, the variations in the structure must be connected to the differences in the soil.
Keywords: PHYTOSOCIOLOGY; SEMIDECIDUOUS MESOPHYTIC FOREST; TREE